2022
DOI: 10.3389/fpls.2021.795288
|View full text |Cite
|
Sign up to set email alerts
|

Functional Traits Drive Dispersal Interactions Between European Waterfowl and Seeds

Abstract: Endozoochory by waterfowl is important for a broad range of angiosperms, most of which lack a fleshy fruit. This dispersal function contributes to the formation and maintenance of plant communities and may allow range shifts for plant species under global change. However, our current understanding of what seed or plant traits are important for this dispersal mechanism, and how they relate to variation in waterbird traits, is extremely limited. We addressed this question using a unique dataset identifying the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 72 publications
6
31
0
Order By: Relevance
“…Many previous studies predicting plant dispersal based on morphological dispersal syndromes overlooked such dispersal processes, and their results are thus unreliable (Green et al, 2022; Martín‐Vélez, van Leeuwen, et al, 2021). Of 35 plant species detected in mallard faecal samples in this study we found five (14%) that had not been previously detected in the diets of European Anatidae, and a further three species not previously recorded in the diet of mallards (Almeida et al, 2022, Table 2). This underlines how little we still know about endozoochory by waterfowl, and which plant species are dispersed.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Many previous studies predicting plant dispersal based on morphological dispersal syndromes overlooked such dispersal processes, and their results are thus unreliable (Green et al, 2022; Martín‐Vélez, van Leeuwen, et al, 2021). Of 35 plant species detected in mallard faecal samples in this study we found five (14%) that had not been previously detected in the diets of European Anatidae, and a further three species not previously recorded in the diet of mallards (Almeida et al, 2022, Table 2). This underlines how little we still know about endozoochory by waterfowl, and which plant species are dispersed.…”
Section: Discussionsupporting
confidence: 52%
“…β‐diversity was greatest in spring, as expected given the high number of rare, terrestrial species recorded only in that season. Similar seasonal patterns may be expected for other temperate dabbling ducks, but may differ in other waterfowl guilds, since herbivorous geese are more likely to ingest terrestrial seeds, and diving ducks are more likely to ingest seeds of submerged plants (Almeida et al, 2022). Previous studies using seeds fed to captive ducks showed that gut passage promotes earlier germination and faster establishment of P. pectinatus (Figuerola et al, 2005), and increases germinability of S. litoralis at favourable salinities (Espinar et al, 2004).…”
Section: Discussionmentioning
confidence: 67%
“…By contrast, waterbird endozoochory is not necessarily coupled with propagule production, because propagules can be ingested from sediments long after they were produced (Brochet et al, 2010; Urgyán et al, 2023). Thirdly, body size plays a more important role for frugivores than for waterbirds, as only species with a large gape can disperse plants with the largest fruits, whereas body size is not correlated with seed size in waterbirds and other non‐frugivores (Almeida et al, 2022; Chen & Moles, 2015). Larger waterbirds have a greater surface area available for epizoochory, but there is no evidence that this influences the probability of dispersal events (Coughlan et al, 2017; Raulings et al, 2011).…”
Section: How Do Waterbirds Differ From Other Dispersal Vectors?mentioning
confidence: 99%
“…The focus of Figuerola and Green (2002) was on aquatic ecosystems, but it has since become clear that waterbirds also disperse many terrestrial plants (Almeida et al, 2022; Kleyheeg et al, 2016; Lovas‐Kiss et al, 2019; Soons et al, 2016). Waterbirds play a major role in moving propagules within and between terrestrial and aquatic habitats.…”
Section: Introductionmentioning
confidence: 99%
“…Waterbirds can occur in high densities as a result of large population sizes and seasonal aggregations (Wetlands International 2022). Although waterbirds disperse a wide range of plants in aquatic, riparian and terrestrial habitats (Soons et al 2016, Green et al 2021, Almeida et al 2022), they interact most strongly with plants more typical of aquatic habitats (Kleyheeg et al 2017) by foraging on their leaves and seeds. This suggests a strong potential for (co)evolution between waterbirds and seed traits of plants in more aquatic habitat types, as indicated by higher Ellenberg F indicator values for preferred soil moisture (Ellenberg et al 1992).…”
Section: Introductionmentioning
confidence: 99%